PENGARUH BERMAIN GAME ONLINE TERHADAP KESEHATAN DAN KONSENTRASI BELAJAR ANAK - Makruf, Anas (Akademi Kebidanan Harapan Bunda Bima, 2025)
The rapid advancement of Information and Communication Technology (ICT) has led to a significant increase in online gaming among adolescents, raising concerns about its impact on academic performance. This study investigated the influence of online gaming on the learning concentration of 100 high school students (aged 16-18) at SMAN 1 Soromandi, Bima Regency, utilizing a quantitative, cross-sectional design. Data were collected through questionnaires assessing online gaming habits and learning concentration levels. Results revealed that while a majority of students exhibited normal gaming patterns (57%), a substantial 43% displayed abnormal habits. Furthermore, 42% of students reported poor learning concentration. Statistical analysis (Chi-Square test) demonstrated a significant negative influence of online gaming on learning concentration (p=0.00), indicating that excessive gaming is associated with reduced focus. These findings underscore the need for targeted interventions by educators and parents to mitigate the detrimental effects of online gaming on students' academic engagement and success, promoting healthier digital habits.